A strategy in deep eutectic solvents for carbon nanotube-supported PtCo nanocatalysts with enhanced performance toward methanol electrooxidation. (26th October 2017) - Zhang, Jun-Ming; Sun, Sheng-Nan; Li, Yang; Zhang, Xiao-Jie; Zhang, Pan-Yu; Fan, You-Jun
Abstract: We herein report a novel strategy for multi-walled carbon nanotube (MWCNT)-supported PtCo nanocatalysts, which are synthesized in deep eutectic solvents (DESs) by a chemical reduction route. The X-ray diffraction (XRD) and transmission electron microscopy (TEM) results indicate that the alloyed PtCo nanoparticles of ca. 2.4 nm are deposited on the surface of MWCNTs with less aggregation in larger clusters. X-ray photoelectron spectroscopy (XPS) measurements reveal the strong charge transfer interaction between Pt and Co atoms in the PtCo/MWCNT catalyst. The electrochemical tests illustrate that the PtCo/MWCNT exhibits much higher electrocatalytic activity, stability and CO tolerance ability than the Pt/MWCNT catalyst for the methanol oxidation reaction (MOR). This study implies that the method based on DESs will be potential in design and fabrication of the highly efficient electrocatalysts for DMFCs applications. Highlights: A strategy in DESs for PtCo/MWCNT nanocatalysts is reported. The alloyed PtCo nanoparticles with small sizes are deposited on the MWCNT surface. There is strong electron interaction between Pt and Co on the catalytic surface. The PtCo/MWCNTs exhibit much higher electrocatalytic performance for MOR.